IPEX and the role of Foxp3 in the development and function of human Tregs - Séverine Le Bras; Raif S. Geha (The Journal of Clinical Investigation, 2006)
Genetic defects in the transcription factor forkhead box protein P3 (Foxp3) cause immune dysregulation, polyendocrinopathy, enteropathy, X-linked (IPEX). IPEX is thought to be due to a defect in naturally arising CD4+ Tregs. In this issue of the JCI, Bacchetta and colleagues demonstrate that patients with IPEX and missense mutations in Foxp3 provide insight into the role of various domains of Foxp3 in the development and function of Tregs (see the related article beginning on page 1713).